Cardiovascular pharmacology : endothelial control - Vanhoutte, Paul M. (Advances in pharmacology (San Diego, Calif.), 2010)
Cardiovascular disease remains a major cause of death and disability in developed countries and, increasingly so, in the developing world. Presented in this volume of Advances in Pharmacology are some of the most promising possibilities for treating large numbers of individuals afflicted with these conditions This volume contains up-to-date reviews of the most important emerging cardiovascular therapies written by world leaders in the field.